Hybridization and postcolonialism - Andrade, Pedro José de Oliveira (2014)
Publicado em: "Colonialisms, post-colonialisms and lusophonies: proceedings of the 4th International Congress in Cultural Studies". ISBN  978-989-98219-2-7